PENGARUH PENDAPATAN PRODUK SAMPINGAN, BIAYA KUALITAS DAN BIAYA OPERASIONAL TERHADAP PROFITABILITAS PERUSAHAAN - Luayyi, Sri; Fitri, Novita Surya; Awalina, Putri (Jurnal Ilmiah Cendekia Akuntansi; Vol 8 No 2 (2023): AprilDO - 10.32503/cendekiaakuntansi.v8i2.3209, 2023)
Profitability is a measuring tool to determine the level of success of a company in obtaining profits. One of the causes of increasing profits in the company is the high revenue and the suppression of existing expenses, such as quality costs and operational costs. The company's income does not only come from by-products but also from by-products. The purpose of this study was to determine the effect of by-product income, quality costs, and operational costs on company profitability (ROA). The data analysis technique used in this study is multiple linear regression which has previously been tested by testing the classical assumptions. The results of the study show that partially and simultaneously by-product income, quality costs and operational costs have a significant effect on profitability, so the decision rule is that Ho is rejected and Ha is accept. Keywords: by-product income, quality costs, operating costs, profitability.